Plasma and complement proteins are essential for the antimicrobial activity of canine platelet lysate - Mollabashi, Melikasadat; Klopfer, Alonza; Lunardon, Thainá; Darzenta, Nikolia; Davis, Emily; Murray, Matt; Sumner, Scarlett M.; Naskou, Maria C. (Frontiers in Veterinary Science, 2025)
IntroductionPlatelet derived products have gained increasing attention as promising alternative biologicals for the treatment of canine wounds. Specifically, platelets play a crucial role during the inflammatory phase of wound healing due to the release of chemokines, proteins, cytokines, and growth factors. Additionally, platelets possess antimicrobial properties, which can be influenced by their manufacturing process, platelet and leukocyte concentration, activation method, and the presence of plasma and complement. The objective of this study was to assess how various preparation methods of platelet products affect their antimicrobial effect against bacteria commonly isolated from wounds.MethodsIn this study, blood was collected from eight purpose-bred dogs, and platelet-rich plasma was produced using two methods of centrifugation, one leukocyte-enriching and one leukocyte-reducing. Some samples were processed for plasma depletion and platelet lysate was subsequently generated through freeze–thaw cycles. Additionally, portions of platelet lysate samples underwent heat treatment for complement inactivation. All treatment groups were tested against four common bacteria found in canine skin wounds: Escherichia coli, Enterococcus faecalis, Staphylococcus pseudintermedius, and Staphylococcus aureus. The antimicrobial effect of various lysate formulations was evaluated using a bacteria-spiking (time-killing) assay.ResultsPlatelet lysate significantly reduced the number of S. aureus and E. coli after 3 h compared to culture media. No significant differences were noted in the log reduction of bacteria between the centrifugation techniques. After depleting plasma, the log reduction of S. pseudintermedius was significantly less than before plasma depletion, whereas the opposite was seen for E. faecalis after 3 h. Complement-depleted plasma led to a significantly lower log reduction for E. faecalis after 24 h compared to platelet lysate.DiscussionTherefore, the presence of plasma and complement proteins in platelet lysate appear to play a critical role in inhibiting the growth of certain bacterial strains, whereas the leukocyte concentration does not have a significant effect. Further research is needed to identify the ideal formulation and dose of canine platelet lysate as an antimicrobial and wound healing treatment.